Swedish children and youth during the COVID-19 pandemic: Evidence from research on childhood environment, schooling, educational choice and labour market entry - Mattias Engdahl; Caroline King Barnard Hall; Helena Holmlund; Martin Lundin; Hanna Mühlrad; Björn Öckert (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2021)
Based on previous research, available statistics and current information on the COVID-19 pandemic, this report analyses and discusses possible consequences of the ongoing pandemic for Swedish children and youth, in the short and longer term. The pandemic is discussed in five chapters focusing on (1) the impact on childhood environment and human capital development, (2) the consequences for children's development and school performance due to increased absenteeism among children, students and teachers in preschools and schools, (3) the effects of distance education, (4) the impact on the demand for education, and (5) consequences for labour market entry and long run labour market outcomes. It is too early to draw firm conclusions about the long-term consequences of the coronavirus pandemic, and yet our overall conclusion is that the pandemic has negative consequences for many children and young adults. Children and youth from disadvantaged environments, with a weak socio-economic background and an inadequate social safety net, are more likely to be severely affected. There are therefore reasons to safeguard and develop the institutions, such as prenatal and child healthcare, social services and school health programs that provide services for children and youth. Moreover, the education system has an important task in compensating for shortcomings in human capital development and lost opportunities caused by the pandemic.
Keywords: 330; Kinder; Jugendliche; Soziale Lage; Schweden